Major Causes of Preventable Death in Trauma Patients - Youngeun Park; Gil Jae Lee; Min A Lee; Kang Kook Choi; Jihun Gwak; Sung Youl Hyun; Yang Bin Jeon; Yong-Cheol Yoon; Jungnam Lee; Byungchul Yu (Journal of Trauma and Injury)
Purpose Trauma is the top cause of death in people under 45 years of age. Deaths from severe trauma can have a negative economic impact due to the loss of people belonging to socio-economically active age groups. Therefore, efforts to reduce the mortality rate of trauma patients are essential. The purpose of this study was to investigate preventable mortality in trauma patients and to identify factors and healthcare-related challenges affecting mortality. Ultimately, these findings will help to improve the quality of trauma care. Methods We analyzed the deaths of 411 severe trauma patients who presented to Gachon University Gil Hospital regional trauma center in South Korea from January 2015 to December 2017, using an expert panel review. Results The preventable death rate of trauma patients treated at the Gachon University Gil Hospital regional trauma center was 8.0%. Of these, definitely preventable deaths comprised 0.5% and potentially preventable deaths 7.5%. The leading cause of death in trauma patients was traumatic brain injury. Treatment errors most commonly occurred in the intensive care unit (ICU). The most frequent management error was delayed treatment of bleeding. Conclusions Most errors in the treatment of trauma patients occurred in early stages of the treatment process and in the ICU. By identifying the main causes of preventable death and errors during the course of treatment, our research will help to reduce the preventable death rate. Appropriate trauma care systems and ongoing education are also needed to reduce preventable deaths from trauma.